2020
DOI: 10.3390/membranes10010014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of the Impact of Pulsed Electric Field Parameters (Pulse/Pause Duration and Frequency) on ED Performances during Acid Whey Treatment

Abstract: Processing acid whey is still a challenge for the dairy industry due to its high lactic acid and mineral contents. Their removal processes represent a high investment and running cost in addition to significant production of polluting effluents. A previous study showed that the use of electrodialysis with the application of pulsed electric fields (PEFs) was sufficiently efficient to produce dryable acid whey with reduced scaling issues during the process. In the present work, eight PEF conditions using differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
(79 reference statements)
2
23
0
Order By: Relevance
“…In Dufton et al, 64% of demineralization was reached after 180 min with the CACAC configuration, mainly in the underlimiting condition. In the present study, a higher demineralization rate (77.2%) was obtained in 30 min in the overlimiting current [41]. These results confirmed that in the overlimiting current condition, EVs generated at the AEM can lead to a better demineralization of acid whey, as presumed in the literature [22,33].…”
Section: Conductivity Evolution and Demineralisationsupporting
confidence: 91%
“…In Dufton et al, 64% of demineralization was reached after 180 min with the CACAC configuration, mainly in the underlimiting condition. In the present study, a higher demineralization rate (77.2%) was obtained in 30 min in the overlimiting current [41]. These results confirmed that in the overlimiting current condition, EVs generated at the AEM can lead to a better demineralization of acid whey, as presumed in the literature [22,33].…”
Section: Conductivity Evolution and Demineralisationsupporting
confidence: 91%
“…It should be noted that the frequencies at which the maximum mass transfer rate for a given membrane is observed become quite small (<0.1 Hz), and the optimal duty cycle for almost all membranes becomes 1/2. The optimal value of the duty cycle equal to 1/2 at overlimiting currents was also determined in [31,37], including the case of using homogeneous Neosepta membranes in electrodialyzers [58,59]. Probably, the surface inhomogeneity of the MK-40 membrane leads to the shift in the optimal frequency to a relatively low-frequency range.…”
Section: The Study Of Mass Transfer Ratementioning
confidence: 99%
“…The essence of the electrodialysis desalination of solutions using PEF modes is to alternate cycles of switching on and off the external electric field. It allows the reduction in concentration polarization and, as a result, increase in mass transfer rate [24,27,28], reduction in the rate of water dissociation at the membrane/depleted solution boundary [29], as well as the rate of precipitate formation in the electrodialyzer chambers during the processing of multicomponent solutions [30][31][32]. Nevertheless, energy consumption in the PEF mode should be greater [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this special cleaning agent containing a surfactant and metal-chelator is very effective for treating the tobacco extract. To increase the viability of electrodialytic desalting of tobacco extract, an elaborate pretreatment [ 27 ] and other mitigation strategies such as reversal ED or pulsed electric field [ 46 , 47 , 48 , 49 ] need to be further developed.…”
Section: Resultsmentioning
confidence: 99%